We want to make abs((x^2+x-4)-8) < epsilon
We control delta and abs(x-3) < delta
Note that:
abs((x^2+x-4)-8) =abs(x^2+x-12)
= abs((x+4)(x-3))
= abs(x+4) abs(x-3)
We control abs(x-3) and so, indirectly, we control abs(x+4)
Make abs(x-3) < 1 . (Any positive number will work in place of 1, but the details of what follows will change.)
This assures us that 2 < x < 4.
So considering x+4 ( the other factor), we see:
6 < x+4 < 7. And
abs(x+4) < 7.
So, if abs(x-3) < 1, then
abs((x^2+x-4)-8) = abs(x+4) abs(x-3) < 7abs(x-3)
If we also make sure that abs(x-3) < epsilon/7, then we will have:
abs((x^2+x-4)-8) < 7abs(x-3) < 7(epsilon/7) = epsilon.
Now write the proof :
Given epsilon > 0, let delta =min {1, epsilon/7}.
Now is abs(x-3) < delta, we will have:
abs((x^2+x-4)-8) = abs(x^2+x-12) = abs(x+4) abs(x-3)
< 7 (epsilon/7) = epsilon